Over-qualification of immigrants in the UK - Szilvia Altorjai (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper uses the first wave of Understanding Society, the UK Household Longitudinal Study (UKHLS), to assess whether or not male migrant workers in the UK are more likely to be over-qualified than the UK born. It also explores whether immigrants from different countries and arriving under different immigration policy regimes vary in their probability of over-qualification. The results suggest that both country of origin (sending factor) and immigration policy (selecting factor) matter and that the greater probability of immigrants' over-qualification masks significant group heterogeneities. Thus, the mechanisms that lead to over-qualification may vary for different groups of immigrants.
Keywords: F22; J15; J24; J61; K37; 330; immigration; over-qualification; immigration policy